Women’s Knowledge of Good Nutrition and Feeding Practices Is Correlated with Their Level of Exposure to Awareness-Raising Activities in Ouagadougou - Mélanie Antoine; Stéphanie Zoungrana; Jérôme W. Somé; Hermann B. Lanou; Séni Kouanda; Claire Mouquet-Rivier (Proceedings)
Malnutrition still affects the population in low-income countries. In Burkina Faso, the estimated prevalence of anemia is high among preschool-aged children and women of childbearing age (83.4% and 53%, respectively in 2014). As part of the MERIEM fortification project, a survey was carried out in 2022 in Ouagadougou to describe dietary practices and women’s knowledge. The aim of this work is to assess the association between exposure to nutrition sensitization campaigns and women’s knowledge of nutrition. A cross-sectional survey conducted in Ouagadougou in March 2022 involved 794 randomly selected women. Socio-economic data were collected, and knowledge scores on breastfeeding (BF; max 9), complementary feeding practices (IYCF; max 8) and nutritional status (NS; max 7) of young children, the feeding practices of pregnant (PW; max 4) and breastfeeding women (BW; max 4), and fortified products (FP; max 18) and vitamins and minerals (VM; max 13) were calculated. Exposure to nutrition sensitizations was categorized as low, moderate, or high. Linear regression models (performed with R software version 4.3.0) were used to analyze the association between knowledge scores and household wealth quintiles, as well as the association between knowledge scores and sensitization scores from the MERIEM project, adjusted for wealth quintiles. Mean scores measured in the sample are 4.7, 2.9, 2.6, 1.4, 1.8, 2.7, and 3.1 for BF, IYCF, NS, PW, BW, FP, and VM, respectively. Knowledge scores increased significantly (p < 0.001) with socio-economic status, except for NS, PW, and BW scores. In total, 78.0% of women had a low level of awareness and only 6.3% had a high level. Exposure to nutrition awareness campaigns increases all women’s knowledge, but not for breastfeeding. This is probably due to the wide promotion of breastfeeding practices among the population, particularly in health centers. The MERIEM-specific project’s awareness-raising activities are overall not associated with knowledge scores. However, there was a significant association with IYCD and VM scores (p < 0.05). Knowledge of diet and nutrition is overall low in Burkina Faso. Raising awareness seems to have a positive effect on knowledge levels and can be a lever in the fight against malnutrition. Further research is needed to determine whether improved knowledge scores translate into improved practices.